The Importance of Hinduism And Cultural Education Role Through Customary Village-Based Non-Formal Education to Maintain the Integrity of Bali - Suardana, I Ketut; Sukarlinawati, Wayan; Suwendra, I Wayan (International Journal of Multidisciplinary Sciences, 2023)
This study refers to the problem background, namely (1) Hindu religious and cultural education in a formal school is very minimal, (2) the quality of young Hindu human resources is low, (3) there is no market-based Hindu religious and cultural education in traditional villages (4) the lack of government attention in the implementation of Hindu religious and cultural education. This study aimed (1) to find solutions to the limitations of obtaining Hindu religious and cultural education in a formal school, (2) to find out how important the role of Hindu religious and cultural education based on pasraman in Customary villages is to improve the quality of young Balinese Hindu human resources, (3) to find out how the implementation of pasraman-based Hindu religious and cultural education in Customary villages, (4) to find out the role of the Balinese government in organizing Hindu religious and cultural education based on pasraman in Customary villages. This study used qualitative research. Data collection used observation and interview methods. The analysis results showed that Hindu religious and cultural education based on pasraman in customary villages had a crucial role in improving the quality of young Hindu human resources to maintain Bali’s constancy. The study concluded that implementing Hindu religious and cultural education based on pasraman in customary villages could embody the character of young Hindu human resources who were virtuous and loved their culture. Therefore, Bali would be maintained its sustainable culture.